The Sacred Significance of Tuvan Personal Names: Tradition and Modernity - Suvandii, Nadezhda (The New Research of Tuva, 2025)
This article examines the sacred personal names of the Tuvan people that are associated with beliefs and traditions historically observed when naming their children. The source base for the study includes personal names found in folklore texts, as well as information gathered by the author from local informants during linguistic field expeditions conducted across various khojuuns (districts) of the Republic of Tuva over different years. Additionally, statistical analysis has been employed using data from Tuvastat on the frequency and distribution of these names in the Tuvan naming system over the past five years.The analysis of personal names with sacred connotations has identified the following lexico-semantic groups: anthroponyms related to shamanism; personal names connected to Buddhism; protective and apotropaic names; and names with ethnocultural significance.The study concludes that traditional naming practices have been largely preserved. Some groups have diminished in usage (e.g., shamanism-related anthroponyms), others have undergone transformation (e.g., names of dedication), while certain categories are currently expanding in use (e.g., names associated with Buddhism and Tibetan culture).
Keywords: onomastics; anthroponym; personal name; naming tradition; sacred; Tuvans; Tuvan culture